Modification of the nuclear pleomorphism score in the Modified Bloom-Richardson grading for invasive breast cancer - Azam Hilmi Mohd Zain; Seoparjoo Azmel Mohd Isa; Nur Asyilla Che Jalil; Suhaily Mohd Hairon; Syed Sana Abrar (PLoS ONE, 2025)
Objective To improve prognostic assessments in breast cancer by evaluating the efficacy of the modified Nottingham grading system, specifically focusing on nuclear pleomorphism through measurements of largest nuclear size (LNS) and nuclear size difference (NSD). Methods This cross-sectional study involved 140 invasive breast cancer cases at Hospital Universiti Sains Malaysia. The study consisted of two phases: Phase 1, which developed nuclear scoring criteria using histopathological images from 2013–2017, and Phase 2, which validated these criteria on cases from 2018–2019. Two sets of samples were included for the study, with 120 cases analyzed in Phase 1 and 53 cases in Phase 2. Descriptive statistics and normality tests assessed differences in LNS and NSD across original nuclear grades. Results Significant differences were found in LNS and NSD across original nuclear grades (p < 0.05), with fair to moderate agreement between the modified grading system and pathologist assessments (Kappa = 0.367). Conclusion Incorporating LNS and NSD into the assessment of nuclear pleomorphism shows potential to improve objectivity in breast cancer grading. However, further validation using larger datasets and automated image analysis is necessary to refine this approach and assess its clinical applicability..